SMU Lee Kong Chian School of Business ranked 8th among Asia Business Schools in Financial Times’ EMBA Ranking 2020 - Singapore Management University (Institutional Knowledge at Singapore Management University, 2020)
Singapore Management University’s (SMU) Lee Kong Chian School of Business (LKCSB) has been ranked 22nd in the Financial Times’ (FT) 2020 global ranking of Executive Master of Business Administration (EMBA) programmes. It holds the 14th spot among Asia universities and ranked 8th among Asia business schools.